Characterizations of PM2.5-bound organic compounds and associated potential cancer risks on cooking emissions from dominated types of commercial restaurants in northwestern China. (December 2020) - Xu, Hongmei; Ta, Weiyuan; Yang, Lin; Feng, Rong; He, Kailai; Shen, Zhenxing; Meng, Zhaojun; Zhang, Ningning; Li, Yaqi; Zhang, Yue; Lu, Jiaqi; Li, Xuan; et al.
Abstract: Cooking emissions are both indoor and outdoor sources for fine particulate matter (PM2.5) but their contributions are often ignored. The PM2.5-bound organic compounds, including alkanols, alkanes, monocarboxylic acids, dicarboxylic acids, and polycyclic aromatic hydrocarbons (PAHs) were determined in the emissions from the most popular types of restaurants in the capital city of northwestern China. The mean concentration of total quantified organic compounds (ΣPM_O ) ranged from 1112 to 32, 016 ng m-3, with the maximum for the Chinese barbecue restaurants. The ΣPM_O accounted for an average of 11% of PM2.5 mass, demonstrating their significances in the cooking emissions. Hexadecanoic acid (C16 ) and 1-hexadecanol (C16 ) were considered as the tracers for stir-frying, steaming, and boiling which are usually applied in the traditional Chinese cuisines; 1-undecanol (C11 ), 9-fluorenone, and indeno[1, 2, 3-cd]pyrene were found to be potential markers for grilling and deep-frying which are widely applied in the Western style cooking method. The PAH diagnostic ratios also illustrated their representatives to distinguish the emissions from traditional Chinese cuisines and the Western-style restaurants. The estimated carcinogenic risks for the restaurants that consumed a large amount of oils and employed high temperature cooking methods (e.g., barbecuing and deep-frying) were 2.6–4.2 times exceeded the international safety limit. The organic profiles obtained in this study could be contributed to refine PM2.5 source apportionment in urban areas in northwestern China. The estimations of potential cancer risks urge the establishment of more stringent legislations to protect the health of the catering staffs. Graphical abstract: Image 1 Highlights: Distinguish PM2.5 -organic profiles were shown in emission of 7 types of restaurants. The average quantified organics was 15, 413 ng m − 3, accounting for ∼11% of PM2.5 . 1-Undecanol, oleic acid and 9-fluorenone are markers for oil-based cooking emission. 1-Hexadecanol and hexadecanoic acid are markers for water-based cooking emission. Cancer risks for barbecue and fast food restaurants were 3 times over the threshold.